Recent issues in world development - Streeten, Paul (ed.) (Oxford, 1981)
From time to time the international journal WORLD DEVELOPMENT publishes survey articles whose purpose is threefold: to present a review of recent research in a number of areas of development policy, to appraise this research critically and to highlight spheres in which work still needs to be carried out. All authors of this collection, edited by Paul Streeten and Richard Jolly, have been encouraged to be interdisciplinary in their approach and to draw particular attention to conclusions relevant to policy rnakers and to solving the practical problems. An important feature of this collection is the commentary by distinguished contributors on individual articles. Additionally each survey article provides a guide to literature which cumulatively presents more than 2,000 references.
Keywords: Economic development